tmdigest a technology management portal - Lu, Norman T. (University of the Philippines Diliman, 2004)
There is a growing demand for technology management has brought to fore the need for more information about the subject. It is in response to this issue that the concept of a technology management portal was developed. The *tmdigest portal is an interactive, electronic knowledge base on technology management. It processes and delivers information using a mix of open source technology tools, including a robust, database-driven content management system on top of a Linux-based/MySQL/PHP web server platform. This in mind, the *tmdigest portal was launched as a means of supplementing the needs of students, faculty, professionals and anyone with an interest in technology management. An initial survey was conducted within the universe of TM students of UP-TMC and the results showed a need for alternative sources of information, and general sharing of information about technology management. While this smacked on knowledge in-breeding, it became the starting point of www.tmdigest.org. Today, interest in technology management continues to grow, evidenced by the growing number of technology management students accepted and enrolled at the University of the Philippines-Technology Management Center (UP-TMC). After initial surveys and interviews were conducted, the website was developed and launched, with a working version 1.0 going live on the Internet in late August 2004. The site was then announced to the public via word of mouth and e-groups. In its present state, the *tmdigest portal is receiving contributions from registered users. To date, 21 individuals have signed up to contribute content for the portal. Of that number, 7 users have signified their willingness to be a site editor. The future outlook of *tmdigest is filled with promise. The site is projected to evolve into a valuable resource center, built and maintained by a community of practice (its user base). A detailed outlook is presented in the last portion of this report. This project was made in partial fulfillment of the requirements of the Masters degree in Technology Management degree granted by the UP-TMC.